Developing Intervention Strategies to Optimise Body Composition in Early Childhood in South Africa. (16th January 2017) - Draper, Catherine E.; Tomaz, Simone A.; Stone, Matthew; Hinkley, Trina; Jones, Rachel A.; Louw, Johann; Twine, Rhian; Kahn, Kathleen; Norris, Shane A.
Abstract : Purpose . The purpose of this research was to collect data to inform intervention strategies to optimise body composition in South African preschool children. Methods . Data were collected in urban and rural settings. Weight status, physical activity, and gross motor skill assessments were conducted with 341 3–6-year-old children, and 55 teachers and parents/caregivers participated in focus groups. Results . Overweight and obesity were a concern in low-income urban settings (14%), but levels of physical activity and gross motor skills were adequate across all settings. Focus group findings from urban and rural settings indicated that teachers would welcome input on leading activities to promote physical activity and gross motor skill development. Teachers and parents/caregivers were also positive about young children being physically active. Recommendations for potential intervention strategies include a teacher-training component, parent/child activity mornings, and a home-based component for parents/caregivers. Conclusion . The findings suggest that an intervention focussed on increasing physical activity and improving gross motor skills per se is largely not required but that contextually relevant physical activity and gross motor skills may still be useful for promoting healthy weight and a vehicle for engaging with teachers and parents/caregivers for promoting other child outcomes, such as cognitive development.